Sunshine and suicide at the tropic of Capricorn, São Paulo, Brazil, 1996-2004 Luz solar e suicídio no trópico de Capricórnio, São Paulo, Brasil, 1996-2004 - Kennedy A. Nejar; Isabela M Benseñor; Paulo A. Lotufo (Universidade de São Paulo, 2007)
Several studies have confirmed seasonal variation in suicide rates according to hours of sunshine. The suicide pattern was assessed in São Paulo, southeastern Brazil, at the tropic of Capricorn from 1996 to 2004. Poisson regression was employed to estimate parameters of seasonality, as well as to verify associations for each day between daylight duration and suicide. During the nine-year study period, there were 3,984 suicides (76.9% in men; median age=38.7 years old). Seasonal averages of suicides were similar, as were monthly averages. Poisson regression did not reveal any association between suicide rates and hours of sunshine (p=0.45) for both sexes. In conclusion, no seasonal pattern was observed for suicides. Estudos epidemiológicos têm confirmado que as taxas de suicídio apresentam variação sazonal relacionada às horas de insolação. O padrão de suicídios foi analisado na cidade de São Paulo, Brasil, no trópico de Capricórnio, de 1996 a 2004. A regressão de Poisson foi utilizada para estimar padrões de sazonalidade, bem como verificar a associação dia-a-dia entre duração da insolação e suicídio. Durante os nove anos houve 3.984 suicídios (76,9% homens; mediana de idade=38,7 anos). As médias de suicídio por estação do ano e por mês de suicídio foram similares. Segundo a regressão de Poisson, não houve associação entre insolação e suicídio (p=0,45) para ambos os sexos. Conclui-se que não houve padrão sazonal de suicídios na cidade de São Paulo.